Pengaruh Kinerja Keuangan terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi pada Perusahaan Sub Sektor Media dan Hiburan Periode 2019-2022 - Falabiba, Arina; Paramita, R.A. Sista (Universitas Negeri Surabaya, 2025)
This research aims to examine the effect of financial performance consisting of liquidity proxied by the Current Ratio (CR), profitability proxied by Return on Equity (ROE), and leverage proxied by the Debt to Equity Ratio (DER) on company value in the sub-sector media and entertainment with company size as the moderating variable. Based on the type of research by the scientific discovery method, this research includes quantitative research with a population of media and entertainment sub-sector companies listed on the IDX for the 2019-2022 period. The sampling method uses a purposive sampling method with a sample size of 40 samples from 10 companies. The data analysis technique uses the Moderated Regression Analysis (MRA) test with the help of the SPSS version 18 application. The research results show that the variables profitability and leverage partially positively and significantly influence company value. In contrast, liquidity and company size do not affect company value. In addition, based on the results of the MRA test, the company size variable can strengthen the effect of profitability on company value. However, company size cannot moderate the effect of liquidity and leverage on company value. Media and entertainment sub-sector companies need to pay attention to the company's ability to generate profits and use debt as capital because these two things can influence the high or low level of investors' assessment of the company.